THE IMPACT OF E-SBN IMPLEMENTATION TOWARDS RETAIL GOVERNMENT BOND INVESTMENT - Fajri R Muhammad; Khumairah (UPT Publikasi Ilmiah UNISBA, 2024)
Since May 2018, the Government of the Republic of Indonesia presents Retail Government Securities (SBN) as one of the investment instruments whose ordering system has changed to an electronic system